Distinct Neutralising and Complement-Fixing Antibody Responses Can Be Induced to the Same Antigen in Haemodialysis Patients After Immunisation with Different Vaccine Platforms - Nadezhda Wall; Rachel Lamerton; Fiona Ashford; Marisol Perez-Toledo; Aleksandra Jasiulewicz; Gemma D. Banham; Maddy L. Newby; Sian E. Faustini; Alex G. Richter; Haresh Selvaskandan; Roseanne E. Billany; Sherna F. Adenwalla; et al. (Vaccines)
Background/Objectives: Generalised immune dysfunction in chronic kidney disease, especially in patients requiring haemodialysis (HD), significantly enhances the risk of severe infections. Vaccine-induced immunity is typically reduced in HD populations. The SARS-CoV-2 pandemic provided an opportunity to examine the magnitude and functionality of antibody responses in HD patients to a previously unencountered antigen—Spike (S)-glycoprotein—after vaccination with different vaccine platforms (viral vector (VV); mRNA (mRV)). Methods: We compared the total and functional anti-S antibody responses (cross-variant neutralisation and complement binding) in 187 HD patients and 43 healthy controls 21–28 days after serial immunisation. Results: After 2 doses of the same vaccine, HD patients had anti-S antibody levels and a complement binding capacity comparable to controls. However, 2 doses of mRV induced greater polyfunctional antibody responses than VV (defined by the presence of both complement binding and cross-variant neutralisation activity). Interestingly, an mRV boost after 2 doses of VV significantly enhanced antibody functionality in HD patients without a prior history of SARS-CoV-2 infection. Conclusions: HD patients can generate near-normal, functional antigen-specific antibody responses following serial vaccination to a novel antigen. Encouragingly, exploiting immunological memory by using mRNA vaccines and boosting may improve the success of vaccination strategies in this vulnerable patient population.